The Spirit in Hebrews: Guiding the Community to Further Truth - Westfall, Cynthia Long (2021)
Abstract There are surprisingly few references to the Holy Spirit in the letter to the Hebrews, though there are more than some may recognize. The author of Hebrews believes that the recipients of his letter/sermon should be fully grounded in their communal life in the Spirit, but he is most interested in how the Holy Spirit is exhorting and guiding the community to further truth during their critical time of need. Therefore, it is the content of what the Spirit is communicating that is his focus, and that content contains some of the most profound statements in the letter/sermon. There are possibly seven references to the Holy Spirit in the letter to the Hebrews. Two of them are consistent with the early Christian traditions about the work of the Spirit: three of them concern the Holy Spirit’s confrontation and communication to the readers through Scripture, and two are disputed as references to the Holy Spirit, although, if they apply, they may reflect a perception of the divinity of the Spirit. The importance of the contexts in which the author mentions the Holy Spirit indicates a role for the Holy Spirit in the sermon/letter that extends beyond the texts in which the Spirit is directly referenced.
Keywords: divinity of the Spirit; Hebrews; Holy Spirit